2010
DOI: 10.1037/a0020033
|View full text |Cite
|
Sign up to set email alerts
|

Where do I stand? Examining the effects of leader–member exchange social comparison on employee work behaviors.

Abstract: Taking an approach integrating principles of leader-member exchange (LMX) differentiation with social comparison theory, we contend that subjective ratings by individuals of their LMX compared to the LMXs of coworkers (labeled LMX social comparison, or LMXSC) explain unique and meaningful variance in outcomes beyond LMX and the actual standing of those individuals in the LMX distribution, referred to as relative LMX, or RLMX. Our findings demonstrate that employees' perceptions of LMXSC are positively related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
419
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(433 citation statements)
references
References 75 publications
11
419
2
1
Order By: Relevance
“…By comparing oneself with others, social comparison serves as a fundamental need to fulfill one's quest to discover the reality of themselves based on self-relevant information (Buunk & Gibbons, 2007). Given that social comparison exists in all kinds of organizations (Greenberg et al, 2007), and that employees whom the leader favors appear to be observed by others (Duchon et al, 1986), it is possible for employees to initiate comparisons of LMX relationships, considering the incremental information for evaluating work circumstances that the comparison of one's own LMX relationship with those of others in the same work group provides (Vidyarthi et al, 2010).…”
Section: Theory and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing oneself with others, social comparison serves as a fundamental need to fulfill one's quest to discover the reality of themselves based on self-relevant information (Buunk & Gibbons, 2007). Given that social comparison exists in all kinds of organizations (Greenberg et al, 2007), and that employees whom the leader favors appear to be observed by others (Duchon et al, 1986), it is possible for employees to initiate comparisons of LMX relationships, considering the incremental information for evaluating work circumstances that the comparison of one's own LMX relationship with those of others in the same work group provides (Vidyarthi et al, 2010).…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Moreover, since everybody has the instinct to maintain a positive self-evaluation (Tesser, 1988), followers who have relatively worse LMX relationships might suffer drastically because they cannot reach the targets of the upward social comparison (Collins, 1996). Since people's behaviors are affected by the results of comparison with targets, we would argue that followers with lower-quality LMX relationships tend to take action to restore their positive selfevaluations (Vidyarthi et al, 2010).…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Meta-analytic findings establish beneficial consequences of positive relationships with supervisors (Gerstner & Day, 1997) and detrimental consequences of negative relationships (Skarlicki & Folger, 1997;Mitchell & Ambrose, 2007;Biron, Brun & Ivers, 2008). For example, leader-member exchange (LMX) is positively related to citizenship behaviors (Vidyarthi, Liden, Anand, Erdogan & Ghosh, 2010); perceived supervisory support (PSS) is positively related to in-role and extra-role performance (Shanock & Eisenberger, 2006); abusive supervision is negatively related to job satisfaction and job performance and positively related to workplace deviance (Tepper, 2007).…”
mentioning
confidence: 99%
“…In the third step, the first author constructed an initial codebook, which provided detailed definitions of different subcategories within these five broad themes. We looked for subcategories in the data and by applying an iterative procedure, these subcategories were compared with phenomena in the literature on mentoring and LMX differentiation (e.g., Scandura, 1997;Vidyarthi et al, 2010). These subcategories were then labeled to capture the meaning reflected by each group of comments (e.g., "Enhances Competencies" as a subcategory of "Impact on the Mentor," and "Creates Feelings of Exclusion" as a subcategory of "Impact on Workgroup Members").…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, studies show that such perceptions of differentiations may have positive consequences for the members who are having a special bond with each other. For example, Vidyarthi, Liden, Anand, Erdogan, and Ghosh (2010) show how individuals compare their leadermember exchange (LMX) with the LMXs of coworkers and how these social comparison perceptions explain unique variance in work behaviors. Members who feel they are close to the leader feel a sense of obligation and a desire to reciprocate to this special position, resulting in greater engagement in citizenship behaviors.…”
Section: Mentoring and Organizational Justicementioning
confidence: 99%